Public Policy Vs Local Wisdom: Controlling Forest and Land Fires in West Kalimantan - Awaluddin, M.; Suwitri, Sri; Santoso, R. Slamet (Indonesian Association for Public Administration (IAPA), 2024)
Forest and land fires are a phenomenon that often occurs every year in West Kalimantan. The indicative burned area in West Kalimantan in 2023 reached 154,167 hectares. The incident was 95% caused by humans who manage forests and land. Implementing regulations controlling forest and land fires and needing more protection of local wisdom are problems in tackling forest and land fires. This study aims to analyze the implementation of public policy vs. local wisdom in controlling forest and land fires in West Kalimantan. This research uses qualitative research methods with descriptive analysis. Data collection will be done using observation, interviews, and documentation. Based on the study's results, the West Kalimantan Provincial Environment and Forestry Service monitors and evaluates locations prone to forest and land fires on fire prevention activities such as counselling, making technical instructions, and procuring infrastructure. The limited quantity of human resources and budget, especially during socialization and firefighting, hampers policy implementation. The West Kalimantan government is committed to guiding communities or palm oil entrepreneurs in clearing agricultural land without burning. The flammable condition of peat soil complicates the fire extinguishing process. The government must prepare qualified human resources and a budget to provide continuous assistance and enforce strict sanctions against forest and land-burning perpetrators.